Reimagining the Court of Protection : access to justice in mental capacity law / Jaime Lindsey, University of Essex. - Lindsey, Jaime, 1987- (Cambridge bioethics and law., 2022)
As one of the first researchers authorised to observe hearings and access court files at the Court of Protection, Jaime Lindsey offers an original account and analysis of the workings of this court. Using data collected with the approval from the senior judiciary of the Court of Protection and the Ministry of Justice, this innovative book combines empirical data with theoretical and normative analysis. It takes a socio-legal approach to understanding how the Mental Capacity Act operates in practice to achieve access to justice and situates current debates within an international context, showing how other jurisdictions have been guided by the United Nations Convention on the Rights of Persons with Disabilities. Furthering scholarship across several fields including access to justice, healthcare law and procedural justice theory, this is a timely and pioneering book that argues for a reimagining of the Court of Protection.